Peningkatan Mutu Guru Ipa Melalui Pelatihan Penggunaan Alat Analisis Kolorimetri Sederhana Berbasis Pencitraan Digital dengan Menggunakan Scanner - Chevi Ardiana; Lida Amalia; Sri Mulyaningsih; Tati Kristianti; Dewi Hernawati (Jurnal Pekemas, 2019)
Colorimetry is a quantitative analysis technique for colored samples, which is used to determine composition (concentration). Technological advancements led to the discovery of modern (instrumentation) tools to complete the colorimetric analysis received by UV-VIS spectrophotometers especially in SMA / MA schools. UV-Vis Spectrophotometers are rarely owned because they are expensive. The impact is limited practicum activities in SMA / MA schools even though practical activities are needed to provide proof of a theory. Therefore, alternative laboratory tools are needed to overcome this problem, including a simple digital imaging based colorimetric analysis tool using a scanner. In order for this alternative tool to be known in the school environment, socialization is needed, namely by training and simulation. The training method used to explain the concept of digital imaging-based colorimetric analysis is supported by demonstration examples of determining the content (concentration) of a substance in the sample. This method is used as training in the operation of digital imaging techniques by using a scanner to obtain images from the sample. Simulation method is used to indicate a software application that can be used to change the image of the imaging results into light intensity (I) then convert to light absorption value (absorbance). It can be concluded that the digital imaging technique using a scanner can be used as an alternative tool to replace UV-Vis spectrophotometer in determining the content (concentration) of substances in the sample and as a support for science / Biology / Chemistry learning in schools. The response of the participants who participated in this activity was very good and they were motivated to apply it in school